2015
DOI: 10.1007/s11130-015-0514-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Anthocyanin Composition to Total Antioxidant Capacity of Berries

Abstract: The present study aimed to evaluate the contribution of anthocyanin composition to the total antioxidant capacity (TAC) of berries having different anthocyanin composition; blackberry, black currant, and blueberry. Blackberry demonstrated the highest TAC, while it had the lowest total anthocyanin content among the three berries in both of the phenolic extract and anthocyanin fractions. On the other hand, black currant had the highest total anthocyanin content, but the lowest TAC. Cyanidin-3-O-glucoside (cya-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 26 publications
2
49
0
3
Order By: Relevance
“…It has been suggested that anthocyanins are the major contributors to the TAC of berries [34], nevertheless, it would be interesting to further analyze if they are also mainly responsible for other biological activities reported for strawberries, how the structure could affect these properties and what are the potential synergistic interactions among the anthocyanins. It would also be interesting to evaluate the biological properties of the metabolites resulting from the digestion of these compounds, since it has been demonstrated that anthocyanin bioavailability is relatively low (relative urinary excretions, ranging from 0.004% to 0.1% of the intake) compared to other polyphenols [29,35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that anthocyanins are the major contributors to the TAC of berries [34], nevertheless, it would be interesting to further analyze if they are also mainly responsible for other biological activities reported for strawberries, how the structure could affect these properties and what are the potential synergistic interactions among the anthocyanins. It would also be interesting to evaluate the biological properties of the metabolites resulting from the digestion of these compounds, since it has been demonstrated that anthocyanin bioavailability is relatively low (relative urinary excretions, ranging from 0.004% to 0.1% of the intake) compared to other polyphenols [29,35].…”
Section: Discussionmentioning
confidence: 99%
“…BC ( R. nigrum ) are widely recognized for containing high levels of polyphenols, specifically ANC (Figure ) and proanthocyanidins (PAC; Figure ), when compared with other berries (Lee et al., ). Both blackberries and blueberries have lower total ANC concentrations compared to BC (949.4 ± 4.0, 1,562.2 ± 52.4, and 1,741 ± 48.8 mg/100 g, dry weight (DW), respectively; Lee et al., ).…”
Section: Chemistry and Sensory Properties Of Bcmentioning
confidence: 99%
“…BC ( R. nigrum ) are widely recognized for containing high levels of polyphenols, specifically ANC (Figure ) and proanthocyanidins (PAC; Figure ), when compared with other berries (Lee et al., ). Both blackberries and blueberries have lower total ANC concentrations compared to BC (949.4 ± 4.0, 1,562.2 ± 52.4, and 1,741 ± 48.8 mg/100 g, dry weight (DW), respectively; Lee et al., ). Interestingly, a large degree of variability of ANC concentrations was demonstrated among three BC cultivars (“Record,” “Blackdown,” and “Ronix”) with a range from 80 to 476 mg/100 mg fresh weight (FW; Nour et al., ).…”
Section: Chemistry and Sensory Properties Of Bcmentioning
confidence: 99%
See 2 more Smart Citations